Mengungkap Pesan di Balik Kisah Abu Lahab dalam Al-Qur'an Surah Al-Lahab (111): 1-5: Kajian Semiotika Michael Riffatere - Rizal Samsul Mutaqin; Akmalia Salsabila (Lajnah Pentashihan Mushaf Al-Qur'an, 2023)
This research seeks to reveal the message behind the story of Abu Lahab contained in sura Al-Lahab (111): 1-5. This is considered necessary because the Qur’an condemns someone to destruction for his enmity towards the religion of Allah. Surah Al-Lahab was revealed to a living person but passed judgment on events yet to occur, leaving room for repentance. Hence, it contains symbols that require interpretation. The method used is qualitative, emphasizing literature studies, and the obtained data is presented descriptively and interpretatively, utilizing Michael Riffatere’s semiotic approach. The results of this study indicate that Surah Al-Lahab was revealed to Abu Lahab and his wife due to their hostility towards the religion of Allah, their arrogance closing their hearts, their penchant for spreading slander, and provoking others towards evil. Surah Al-Lahab was revealed as a climactic punishment for their deeds in the world. Through this story, Allah reminds humanity not to behave like Abu Lahab, as the punishment outlined in Surah Al-Lahab applies to all those who possess the characteristics of Abu Lahab.